GAS SENSOR DEVELOPMENT FOR COMBUSTIBLE GAS MONITORING - A. P. Grinchuk; I. A. Taratyn; V. V. Khatko (Приборы и методы измерений)
The lines of development of gas sensors having low power consumption have been considered in the article. The utilization of nanostructured alumina as sensor template allows obtaining thermocatalytic and semiconductor gas sensors with low power consumption.